THE ROLE OF AUTHENTIC MATERIALS IN DEVELOPING STUDENTS’ PRAGMATIC COMPETENCE (The Conference Hub, 2025)
This article explores ways to develop students' pragmatic competence, emphasizing the importance of pragmatic knowledge in effective communication. Pragmatic competence refers to the ability to use language appropriately in various social contexts, understanding how to convey and interpret meaning beyond the literal sense. The paper delves into strategies, including explicit teaching, real-life scenarios, interactive tasks, and the integration of cultural awareness in language learning.